THE DISTRIBUTION OF FILLER MATERIAL ON BASE METALS DURING BRAZING OF ALUMINUM ALLOYS - Andrei DIMITRESCU (Fiabilitate şi Durabilitate, 2013)
Since aluminum brazing technology is relatively new compared to other permanent joiningtechnologies, this technological process needs a scientific approach.One of the specific parameters of this type of technological processes is the distribution of fillermaterial on base material. This parameter affects directly the quality of the brazed assembly